Analysis of student and student interest in the Darmajaya IIB management study program (S1) Concentration in Bandar Lampung - Muhammad Saputra; Aswin (LP2M Politeknik Jambi, 2019)
The aim to be achieved in this research is to study the interests of prospective students and students at the concentration of management study program (S1) Darmajaya IIB in Bandar Lampung. This research is a descriptive research. This research used questionnaire to collect data from 2387 sample consist of Darmajaya 3rd and 5th semester students and external respondents namely SMA / K and MA / I students in 47 schools spread across Bandar Lampung. Based on the results of the distribution of questionnaires conducted and the results of the analysis, obtained information for opening a new concentration of management study program IIB Darmajaya, the recommendation for opening the concentration is the concentration of Hospitality Management, Strategy Management, Operations Management